Analisis Kebutuhan Layanan Pendidikan Terkait Pilihan Peserta Didik Dalam Melanjutkan Pendidikan ke Sekolah Menengah Atas Tahun 2015 - Sutadi Sutadi,; Dali Santun Naga; Yeni Harianto (Dhammavicaya : Jurnal Pengkajian Dhamma, 2021)
Schools as educational institutions should always do quality improvement in the administration of education. Students whoattend school can be seen from the participant's point of view. Educational services needed by students can be done byselecting schools. For this reason, this study discusses the educational needs needed by students in continuing the educationexpected from junior high school to high school. This research uses a qualitative method using case studies. The studyparticipants consisted of six ninth grade students who were returned to secondary education. Data is collected by interviewsconducted based on the purpose of the study. Analysis of interview data using general stages according to McDury. Thefindings of this study include: dimensions of physical evidence, guarantees, and reliability of education services. Learners'needs related to physical factors, the process of teaching and learning activities and learning outcomes that exist in students.Related to schools making planning and supervision that requires the needs and infrastructure, teaching staff, and curriculumby taking into account the aspirations and needs of students to suit the needs of quality educational needs.